Utilizing Natural Resources in Dentistry Practice to Enhance Holistic Oral Well- Being - Nazhifa Najmi Mumtaz Sulaeman (Cerdika: Jurnal Ilmiah Indonesia, 2024)
This study examines the potential of siwak (Salvadora persica) in enhancing holistic oral health through a literature review approach. Siwak, historically utilized across cultures, contains active compounds like trimethylamine, tannins, Salvador, and benzyl isothiocyanate, known for their antibacterial and plaque-inhibiting effects. Research data indicate that siwak effectively reduces plaque buildup and gingival inflammation, supporting its integration into modern dental practices. However, improper use can lead to adverse effects such as gingival recession and tissue trauma, highlighting the need for proper oral hygiene education. The integration of siwak in modern dentistry requires quality control and standardization to ensure its efficacy. Modern applications of siwak, including toothpaste and mouthwash, demonstrate its potential in promoting holistic dental care. Cultural acceptance and regulatory standards are essential for its broader adoption, while public education about its benefits and scientific basis can improve acceptance and utilization.